2008
DOI: 10.1089/jwh.2007.0616
|View full text |Cite
|
Sign up to set email alerts
|

Stress Urinary Incontinence in Women with a History of Gestational Diabetes Mellitus

Abstract: Objective: Stress urinary incontinence may serve as a barrier to lifestyle modification among women at high risk for diabetes, but the prevalence of stress urinary incontinence among women with histories of gestational diabetes mellitus (hGDM) is unknown. The purpose of this study was to examine the prevalence of stress incontinence among women with hGDM and to examine its association with their current physical activity.Methods: We surveyed women with hGDM within the past 5 years who were currently enrolled i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
36
0
2

Year Published

2013
2013
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(40 citation statements)
references
References 24 publications
2
36
0
2
Order By: Relevance
“…In contrast, Kim et al [14] found that 49% of women with a recent history of GDM, reported greater than weekly incontinence, and approximately a quarter reported incontinence that interfered with activity during and after pregnancy.…”
Section: Discussionmentioning
confidence: 90%
See 3 more Smart Citations
“…In contrast, Kim et al [14] found that 49% of women with a recent history of GDM, reported greater than weekly incontinence, and approximately a quarter reported incontinence that interfered with activity during and after pregnancy.…”
Section: Discussionmentioning
confidence: 90%
“…The etiology of UI is multifactorial, but hyperglycemic disorders and pregnancy are recognized as important risk factors. UI prevalence and severity are significantly higher during pregnancy and in women with diabetes mellitus or a history of gestational diabetes mellitus (GDM) [11][12][13][14][15][16].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…também verificaram que 49% das diabéticas gestacionais relataram IU durante a gestação e 28% relataram que esta IU afetava sua atividade diária. Concluíram que a IUE é comum entre mulheres com DMG e parece não estar associada com os níveis de atividade física ou índi-ce de massa corpórea (61).…”
Section: Aumento Da Incontinência Urinária Em Diabéticas Pós-parto Ceunclassified